El acoso sexual callejero, una forma de violencia hacia las mujeres ecuatorianas - Chamaidán Apolo, Liliam Elena (Machala, Utmachala, 2023)
Street sexual harassment has become a social problem, which is expressed more and more frequently; however, it is not contemplated in the Ecuadorian legal regulations. The objective of this article is to analyze the situation of vulnerability of the rightsof Ecuadorian women given by the normative vacuum related to the typification of street sexual harassment within the Comprehensive Criminal Organic Code, for which a descriptive investigation based on the methods was developed: exegetical, document reviewand content analysis. Among the main findings are that street sexual harassment is not defined in any legal regulations. The non-typification of this figure causes a normative legal vacuum that does not allow the judge to apply justice adequately. The analysis, updating and improvement of the Comprehensive Organic Criminal Code is required in order to typify the figure of street sexual harassment, taking into account the components: factual, legal and evidentiary.
El acoso sexual callejero se ha convertido en un problema social, que se expresa cada vez con mayor frecuencia; sin embargo, no es contemplado en la normativa jurídica ecuatoriana. El objetivo de este artículo es analizar la situación de vulnerabilidad de los derechos de las mujeres ecuatorianas dado por el vacío normativo relativo a la tipificación del acoso sexual callejero dentro del Código Orgánico Integral Penal, para lo cual se desarrolló una investigación descriptivasustentada en los métodos: exegético, revisión documental y análisis de contenido. Entre los principales hallazgos se encuentran que el acoso sexual callejero no se encuentra definido en ninguna normativa jurídica. La no tipificación de esta figura ocasiona un vacío jurídico normativo que no permite al juzgador aplicar la justicia de manera adecuada. Se impone el análisis, actualización y perfeccionamiento del Código Orgánico Integral Penalen aras de tipificar la figura del acoso sexual callejero, teniendo en cuenta los componentes: fáctico, jurídico y probatorio.
Keywords: ACOSO SEXUAL CALLEJERO; VIOLENCIA DE GENERO; MARCO JURIDICO; VACIO LEGAL